Preliminary studies on bleaching of whey using ozone as a bleaching agent - Shen, Jiamen; Ma, B.; Amamcharla, Jayendra (My University, 2018)
Annatto is widely used in cheddar cheese manufacture to provide a consistent color and improve consumer preference. Only a portion of annatto added to cheese milk remains in cheese. The rest remains in the resultant liquid whey. Annatto in the liquid whey must be bleached in order to manufacture whey protein-based ingredients. Ozone, as a green bleaching source, has the potential to bleach annatto in liquid whey. The objective of this study was to examine the effectiveness of ozone in terms of holding time, temperature, and recirculation time as a whey bleaching agent. Annatto aqueous solution (0.017%) was prepared and incubated at 10, 20, 35 ℃. After that, the solution was exposed to ozone by pumping through an ozone generator in a continuous mode. The bleaching effect on annatto solution has an absorbance reduction of more than 95%. However, treatment temperature did not affect the bleaching efficiency in water solution. Sweet whey powder was reconstituted to 7.6% concentration and added with 0.017% annatto to simulate commercial cheese whey. Reconstituted liquid Whey was equilibrated to 10, 20, and 35 ℃ for 30 min and exposed to ozone by the ozone generator for 1 and 2 min in recirculation mode. In reconstituted cheese whey, when the circulation time was increased from 1 to 2 min, the absorbance reduction increased from 37% to 70%. On the other hand, when the temperature was increased from 10 to 20℃, the absorbance reduction reached a maximum of 80%. However, a further increase in temperature did not affect the annatto reduction. Overall, treatment temperature and recirculation time were found to be the most important factors that can affect bleaching of liquid whey using ozone.
Keywords: Spring 2018